Chemical composition of natural waters of contaminated area: The case for the Imandra Lake catchment (the Kola Peninsula); IOP Conference Series: Earth and Environmental Science; Vol. 33 : Contemporary Issues of Hydrogeology, Engineering Geology and Hydrogeoecology in Eurasia - Evtyugina Z. A.; Guseva N. V. Natalia Vladimirovna; Kopylova Yu. G. Yuliya Grigorievna; Vorobjeva (Vorobeva) D. A. Darjya Andreevna (Hydrogeochemistry, 2016)
Title screen